Development of the Academic Policy of Universities in Kazakhstan through the Strategy of Authentic Assessment of Students' Educational Achievements - Kelgembayeva, Bakytzhan; Kumarbekuly, Sanat; Aliya, Oskembay; Alimkhan, Aigul; Kaldybay, Kainar; Kadirov, Berik (Journal of Ecohumanism, 2024)
This chapter explores the strategy of authentic assessment of students' educational achievements and its role in the implementation of the academic policy of universities. The research upon which it is based includes a text analysis of the rhetoric of the academic policy of 4 universities in Kazakhstan and several regulatory documents on assessment. We studied the strategy of authentic assessment at the University of Westminster in the UK. The results of the study point to the need to expand and modernize the conceptual apparatus, improve, and revise the principles and strategies of assessment at the universities of Kazakhstan. It also determines the constraints on the transition to authentic assessment.